Faktor-Faktor Yang Mempengaruhi Pendapatan Istri Nelayan di Kota Dobo Kabupaten Kepulauan Aru - Fransisca Riconita Sinay; Silvia Manuhutu (Jurnal Pendidikan Geografi Unpatti, 2025)
This study aims to analyze the participation of fishermen's wives in household income and to identify the factors influencing their income in Dobo City, Aru Islands Regency. The research employed a quantitative approach using descriptive methods and multiple linear regression analysis. Data were collected through questionnaires distributed to fishermen's wives engaged in productive economic activities. The results showed that the average contribution of wives' income to household income was classified as moderate, at 34.37%. Simultaneously, variables such as the wife's working time, work experience, husband's income, and number of family members influenced the wives’ income. Partially, the wife's working time, husband's income, and number of family members had a significant effect, while work experience did not. These findings highlight the economic role of women in fishermen's households and the need for empowerment strategies to enhance productivity and access to economic resources. This study is expected to serve as a reference for gender-based development programs in coastal communities.